The Response of Prostate Smooth Muscle Cells to Testosterone Is Determined by the Subcellular Distribution of the Androgen Receptor - Peinetti, Nahuel (2018)
Androgen signaling in prostate smooth muscle cells (pSMCs) is critical for the maintenance of prostate homeostasis, the alterations of which are a central aspect in the development of pathological conditions. Testosterone can act through the classic androgen receptor (AR) in the cytoplasm, eliciting genomic signaling, or through different types of receptors located at the plasma membrane for nongenomic signaling. We aimed to find evidence of nongenomic testosterone-signaling mechanisms in pSMCs and their participation in cell proliferation, differentiation, and the modulation of the response to lipopolysaccharide. We demonstrated that pSMCs can respond to testosterone by a rapid activation of ERK1/2 and Akt. Furthermore, a pool of ARs localized at the cell surface of pSMCs is responsible for a nongenomic testosterone-induced increase in cell proliferation. Through membrane receptor stimulation, testosterone favors a muscle phenotype, indicated by an increase in smooth muscle markers. We also showed that the anti-inflammatory effects of testosterone, capable of attenuating lipopolysaccharide-induced proinflammatory actions, are promoted only by receptors located inside the cell. We postulate that testosterone might perform prohomeostatic effects through intracellular-initiated mechanisms by modulating cell proliferation and inflammation, whereas some pathological, hyperproliferative actions would be induced by membrane-initiatednongenomic signaling inpSMCs.